2019
DOI: 10.1016/j.worlddev.2019.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Interrogating differences: A comparative analysis of Africa’s informal settlements

Abstract: Urban development in Africa is a very diverse and ambivalent phenomenon with aspects that do not fall neatly into global standards. Informal settlements therefore challenge governance by standards. We argue that quantifying and interrogating differences offers a better basis for governance. By drawing on a comparative analysis of three different informal settlements in Sub-Saharan Africa, this paper explores what differences reveal about the governance of informal settlements. The paper uses an urban societal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 33 publications
0
49
0
Order By: Relevance
“…This policy is not directed at informal settlements but closely affects informal settlement dwellers. Charcoal is used for cooking and heating among lower income households and is the second most used fuel in informal settlements in Nairobi, after paraffin (Kovacic et al 2019). As a result, the ban of charcoal creates a problem for the urban poor with implications for social justice.…”
Section: Charcoal Ban In Kenyamentioning
confidence: 99%
See 1 more Smart Citation
“…This policy is not directed at informal settlements but closely affects informal settlement dwellers. Charcoal is used for cooking and heating among lower income households and is the second most used fuel in informal settlements in Nairobi, after paraffin (Kovacic et al 2019). As a result, the ban of charcoal creates a problem for the urban poor with implications for social justice.…”
Section: Charcoal Ban In Kenyamentioning
confidence: 99%
“…An example of this framing is statistics that report that Africa accounts for one-fifth of the world's population but for less than 4% of global electricity consumption (The Economist 2019). If urban informality is seen as a way of life, the use of paraffin and charcoal should rather be understood as affording flexibility in repurposing cooking stoves (Kovacic et al 2019). In the latter case, energy is part of the informal way of life.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, gender was found to play a significant role in entrepreneurship and access to electricity [14,15], economic growth [29], and energy policy and organisational practices [32]. The interconnectedness of the spheres in which gender plays a significant role reinforces the fact that excluding gendered considerations in innovation could be detrimental to other sustainability efforts.…”
Section: Gender In Contextmentioning
confidence: 99%
“…inequalities and the lack of access to sustainable energy practices are disproportionately affecting women in the developing world [3,14,15].…”
mentioning
confidence: 99%
“…The (ISC) (2020) explains that African cities have a unique but often overlooked capacity to innovate and experiment with solutions for sustainability. These cities often include complex but agile informal settlements and multiple ecologies with resources that offer alternative pathways to the implementation of the global development agenda (Buyana 2019;Kovacic et al 2019). Urama et al (2014) reported that Benin already has policies, strategy and action plans on sustainable development issues in areas, such as water and the environment.…”
Section: Introductionmentioning
confidence: 99%